Pemodelan Aplikasi Pramuka Ambaraka Berbabis Web Menggunakan ISO 25010 - Ariyadi Dwi Saputra; Lathifah Lathifah (Journal of Data Science and Information Systems, 2023)
In this pandemic, many schols and places of learning are carried out online, many things are not understood by students for online learning, either the unavailability of adequate internet services, or the lack of maximum understanding of students when studying online. The Ambaraka website is a platform that provides web-based Scouting lessons that can be accessed by anyone. This Ambaraka website is a learning program aimed at Sman 12 Bandar Lampung schools, The Ambaraka website uses the ISO/IEC 25010 method. ISO/IEC 25010 is the evaluation method used in this study with an evaluation focus on aspects of. Performance Efficiency, analysis using the GTMetrix site with results of 92% Performance with grade B, but in the Structural section it only gets 75% due to the large number of images and the size is too large.